Forward rapidity J/ψ production as a function of charged-particle multiplicity in pp collisions at √s = 5.02 and 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Journal of high energy physics, 2022)
The production of J/ψ is measured as a function of charged-particle multiplicity at forward rapidity in proton-proton (pp) collisions at center-of-mass energies $$ \sqrt{s} $$= 5.02 and 13 TeV. The J/ψ mesons are reconstructed via their decay into dimuons in the rapidity interval (2.5 < y < 4.0), whereas the charged-particle multiplicity density (dNch/dη) is measured at midrapidity (|η| < 1). The production rate as a function of multiplicity is reported as the ratio of the yield in a given multiplicity interval to the multiplicity-integrated one. This observable shows a linear increase with charged-particle multiplicity normalized to the corresponding average value for inelastic events (dNch/dη/〈dNch/dη〉), at both the colliding energies. Measurements are compared with available ALICE results at midrapidity and theoretical model calculations. First measurement of the mean transverse momentum (〈pT〉) of J/ψ in pp collisions exhibits an increasing trend as a function of dNch/dη/〈dNch/dη〉 showing a saturation towards high charged-particle multiplicities.
*The ALICE collaboration: S. Archaya, V. Anguelov, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feulliard, P. Glaessel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 22.07.2022